Juridical Analysis of the Legal Responsibility of Employers for Neglecting Workers' Social Security Rights in Pangkalpinang, Bangka Belitung Province - Defri Maulana; Yandi (Dinasti Research, 2025)
The Job Creation Act aims to create job opportunities, facilitate investment, and enhance Indonesia's economic competitiveness, with one of its main focuses being the regulation of labor and social security for workers. However, the implementation of this law faces several challenges, particularly in protecting workers' rights, such as employers neglecting their obligations to provide social security. In Pangkalpinang, economic factors and a lack of understanding of employers' legal obligations regarding workers' social security are the primary causes of this issue. This study employs a normative legal research method with a statutory and conceptual approach to analyze the urgency of enacting the Job Creation Act and its implications for worker protection in the region. The findings reveal that although the Job Creation Act provides a clear legal foundation, its practical application is hindered by employers' ignorance, who perceive enrolling workers in social security programs as an additional burden. Moreover, ineffective supervision exacerbates the problem. Therefore, to optimize the protection of workers' rights, more intensive education for employers, stricter supervision, and firmer law enforcement are required to ensure workers' social security rights are well-guaranteed in accordance with the applicable regulations.